Developing a Model of Islamic Leadership Quality Using Multiple Case Studies for Takaful Performance - Wan Norhayate, Wan Daud; Fakhrul Anwar, Zainol; Marlisa, Abdul Rahim; Abdul Ghafar, Ismail (2014)
Successful organizations represent a key ingredient for nations around the globe. Although a substantial body of research has focused on the predictors of organizational performance, studies involving its predictors within the context of developing Muslim countries like Malaysia are rather limited. This paper intends to illustrate how Islamic leadership can enhance an organization’s goal accomplishment. Objective: The main objective of the study is to examine the effect of quality of Islamic leadership on organizational performance from Takaful business’ perspectives in Malaysia. Results: Findings from the study found that Islamic leadership qualities have positive effect with Takaful performance. Conclusion: The results further demonstrate that quality of Islamic leadership contribute to the higher performance of Takaful operators in Malaysia.